The Effect of Profitability and Liquidity on Company Value with Capital Structure as an Intervening Variable - A'inatunnadillah, Ningtias; Akhmadi, Akhmadi; Suryani, Emma (Journal of Economics, Management, Accounting and Computer Applications, 2025)
This study aims to test and analyze the influence of profitability and liquidity on the value of companies with capital structure as intervening variables in companies listed in the SMInfra18 Index on the Indonesia Stock Exchange for the 2018-2023 period. The variables studied included profitability proxied by Net Profit Margin (NPM), liquidity with Current Ratio (CR), capital structure with Long-term Debt to Equity Ratio (LTDER), and company value with Tobin's Q. Purposive sampling method was used to obtain eleven companies as a sample with a total of 66 observation data. Data analysis was conducted using IBM SPSS Statistics 23. The results of the study show that profitability and liquidity have a positive and significant effect on the company's value. Profitability and liquidity have a negative and significant effect on capital structure. Capital structure is not able to mediate the influence of profitability on the value of the company, but it is able to mediate the influence of liquidity on the value of the company.